1 min read

Skolematematikk

Start med $\frac{3}{2y}-\frac{3z}{4}-\frac{1}{2}$. N√• bruker vi at vi kan gange med et tall (ulikt $0$) over og under br√łkstreken:

$$\frac{3}{2y}=\frac{3\cdot2}{2y\cdot2}=\frac{6}{4y}$$

$$-\frac{3z}{4}=-\frac{3z\cdot y}{4\cdot y}=-\frac{3zy}{4y}$$

$$-\frac{1}{2}=-\frac{1\cdot2y}{2\cdot2y}=-\frac{2y}{4y}$$

Dermed er

$$\begin{eqnarray*} \frac{3}{2y}-\frac{3z}{4}-\frac{1}{2} & = & \frac{6}{4y}-\frac{3zy}{4y}+-\frac{2y}{4y}\\ & = & \frac{6-3zy-2y}{4y}\\ & = & \frac{-2y-3zy+6}{4y} \end{eqnarray*}$$